2011
DOI: 10.1038/onc.2011.259
|View full text |Cite
|
Sign up to set email alerts
|

Eya2 is required to mediate the pro-metastatic functions of Six1 via the induction of TGF-β signaling, epithelial–mesenchymal transition, and cancer stem cell properties

Abstract: Six1 is a critical regulator of embryonic development that requires interaction with the Eya family of proteins (Eya1-4) to activate the transcription of genes involved in neurogenesis, myogenesis, and nephrogenesis. While expression of Six1 and Eya family members is predominantly observed in development, their overexpression is observed in numerous cancers. Importantly, both Six1 and Eya have independently been shown to mediate breast cancer metastasis, but whether they functionally interact during tumor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
159
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 59 publications
9
159
1
Order By: Relevance
“…Next, we sought to validate the relevance of EYA2 and c-ABL to the antitumor activity of ERβ. Consistent with the previous reports of the oncogenic activity of EYA2 (22,23) in breast cancer, ectopic expression of EYA2 promoted breast cancer cell growth in vitro and in vivo (Supplemental Figure 6, C and D). Using the same systems, we found that knockdown of c-ABL led to accelerated tumor cell growth (Supplemental Figure 6, E and F).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Next, we sought to validate the relevance of EYA2 and c-ABL to the antitumor activity of ERβ. Consistent with the previous reports of the oncogenic activity of EYA2 (22,23) in breast cancer, ectopic expression of EYA2 promoted breast cancer cell growth in vitro and in vivo (Supplemental Figure 6, C and D). Using the same systems, we found that knockdown of c-ABL led to accelerated tumor cell growth (Supplemental Figure 6, E and F).…”
Section: Resultssupporting
confidence: 80%
“…The phosphatase activity of EYA is important for its roles in transcriptional regulation (14,16), cytoplasmic signaling (17), innate immune response (18), and DNA damage-induced apoptosis (19,20). The oncogenic activity of EYA proteins has been demonstrated in ovarian (21) and breast cancers (22,23). In particular, EYA2 was shown to promote proliferation, migration, and invasion of breast cancer cells, but its direct target(s) in tumor promotion is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Six1 is a homeodomain transcription factor (37) and a putative downstream target of Notch2 (24,25). Interestingly, Ford and colleagues showed that Six1 stimulates the malignant transformation of mammary epithelial cells through transactivating cyclin A1 (38,39) and induces EMT in mammary cancer cells through the induction of TGF-b signaling (27,40). These findings suggested that Notch2 and Six1 play coordinate roles during the early-stage lung adenocarcinoma progression.…”
Section: Discussionmentioning
confidence: 94%
“…A further reduction to 38% results in renal hypoplasia, and 14% of the normal Eya1 level is incompatible with kidney formation in mouse mutants (14). On the other hand, abnormally high levels of human EYA1 are linked to breast cancer progression and poor prognosis (7). These observations suggest that cell typespecific Eya1 function may in part depend on its protein levels.…”
mentioning
confidence: 80%